ANALISIS STRATEGI PENGEMBANGAN KOMODITAS UNGGULAN SUB SEKTOR TANAMAN HORTIKULTURA BUAH - BUAHAN DAN SAYURAN TERHADAP PEREKONOMIAN DI KABUPATEN KEBUMEN - Virta Afliqoh, Arzhavi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to identify leading horticultural commodities of fruits and vegetables that are prioritized for development and development strategies for the economy in Kebumen Regency. The data analysis method uses LQ which compares the GRDP of the Regency with the Province and uses SWOT analysis with IFAS and EFAS. Based on the results of the LQ calculation, horticultural fruit crops that become the base sector are Big Orange, Mango, Mangosteen, Passion Fruit, Melon, Banana, Rambutan, Watermelon, and Soursop. While the types of vegetables that become the basic sector are: Red Onion, Spinach, Chili Pepper, Red Bean, Long Bean, Water Spinach, Potato, Cucumber, Cabbage, Petai, Eggplant, and Carrot. Based on the results of the SWOT analysis, there is an aggressive strategy as a strategy for developing superior commodities in the horticultural sub-sector of fruits and vegetables in Kebumen Regency.